Seismic and Tsunamis Vulnerability Assessment of the Shelter School Building Structure with and without Retrofitting - Fauzan; Zev Al Jauhari; Geby Aryo Agista; Yokota, Atsushi; Masharya Eko Putra (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
Understanding the vulnerability of school shelters to tsunamis is crucial for developing effective mitigation strategies and increasing the resilience of coastal communities in the education sector. SDN 02 Sasak Ranah Pasisia, an elementary school in West Pasaman Regency, West Sumatera, Indonesia, had a shelter building constructed in 2010. However, the construction remains incomplete. A structural assessment using current Indonesian building codes and vulnerability analysis is necessary to proceed with construction and ensure the building’s strength against the working loads. Thestructural assessment revealed that several columns could not support the working load, necessitating local retrofitting. In this study, the retrofitting of the building was designed using concrete jacketing. Furthermore, structural fragility curves of the school building were developed before and after retrofitting against earthquake and tsunami loads. The seismic fragility curve was determined from the maximum displacement of the building for varied earthquake acceleration, using nonlinear time history dynamic response analysis scaled using the incremental dynamic analysis method and damage limits defined by ATC-40, characterized by Hazus. Meanwhile, the tsunami fragility curve was determined from the maximum displacement due to tsunami load for each variation of tsunami inundation depth. The vulnerability analysis results indicated that retrofitting the school building with concrete jacketing reduces the probability of building damage due to earthquake loads by 18% at the level of complete damage at a PGA of 0.520 g (based on the Indonesian Seismic Map). Similarly, it reduced the probability of building damage due to tsunami loads by 20%, at the level of complete damage corresponding to a tsunami wave height of 5.00 m for West Pasaman, Indonesia.